A mentally healthy framework to guide employers and policy makers - Mark Deady; Samineh Sanatkar; Leona Tan; Nick Glozier; Nick Glozier; Aimee Gayed; Katherine Petrie; Katherine Petrie; Vita Ligaya Dalgaard; Elizabeth Stratton; Elizabeth Stratton; Anthony D. LaMontagne; et al. (Frontiers Media S.A., 2024)
Mental health problems among the working population represent a growing concern with huge impacts on individuals, organizations, compensation authorities, and social welfare systems. The workplace presents both psychosocial risks and unique opportunities for intervention. Although there has been rapid expansion of workplace mental health interventions over recent decades, clear direction around appropriate, evidence-based action remains limited. While numerous workplace mental health models have been proposed to guide intervention, general models often fail to adequately consider both the evidence base and where best-practice principles alone inform action. Further, recommendations need to be updated as new discoveries occur. We seek to update the Framework for Mentally Healthy Workplaces based on new evidence of intervention effectiveness while also incorporating evidence-based principles. The updated model also integrates concepts from existing alternate models to present a comprehensive overview of strategies designed to enhance wellbeing, minimize harm, and facilitate recovery. Examples of available evidence and obstacles to implementation are discussed. The Framework is designed to support employers and managers in determining which strategies to apply and to guide future avenues of research.